Trivial trauma as a cause of stroke in children - Clara Rilna Joseph; K Shreedhara Avabratha; Rashmi Alva; Raghavendra BS# (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2020)
Ischaemic stroke resulting from minor head injury are rare in children, as trauma usually results in intracranial bleed. We report a case who presented with right sided hemiplegic stroke due to trivial trauma. 11 year old girl who was previously healthy, presented with right sided facial palsy and ipsilateral hemiplegia of one day. MRI brain showed left sided middle cerebral artery territory infarct. MR angiography showed left middle cerebral artery territory infarct involving the left gangliocapsular region, left corona radiata and left frontotemporal lobe, suggestive of occlusion. On enquiry mother revealed fall from stairs 3 days back.